OTONOMI KHUSUS DAN IMPLIKASI YURIDIS LEGISLASI HUKUM ISLAM DI NANGROE ACEH DARUSSALAM (NAD) - Wawan Haryanto; Syamsuddin Sakka (IAIN Palopo, 2021)
Aceh has a very long history of Islam stretching back to the first-century hijriyah. The practice of Islamic teachings, especially the legal aspects, has spread to the government level. This is the historical basis for the implementation of Islamic law in Bumi Rencong. The special autonomy imposed in Aceh is essentially related to the granting of authority to regulate part of the legal order of Acehnese people's lives with Islamic law. This literature research uses a normative legal approach to examine the content of Aceh's special autonomy and its implications for legal legislation. This study finds that Aceh's special autonomy has implications for Islamic law legislation in the form of qanuns as a formal form of the implementation of special autonomy, especially the implementation of Islamic law. Most of the tools for implementing Islamic law have been completed, although there are still shortcomings and challenges. These challenges include incomplete implementation rules and restrictions by other laws and regulations.